3D fast spatial filtering method. (7th October 2011) - Sims, Dave I.; Siadat, Mohammad-Reza; Sethi, Ishwar K.
Spatial image filtering is a method by which an image can be enhanced. The method involves computing correlation of a mask and input image to produce desired image. This requires a number of computations consisting of addition and division operations. Such operations are repeated multiple times for common areas of overlapping masks as we shift the mask over consecutive pixels. As a result, there is a significant number of redundant operations that slows down the spatial filtering process. In this paper, we propose a new method to eliminate redundant operations and we apply it to volumetric MRI images using mean filter. We analyse the complexity of the proposed method and compare its processing speed to that of the conventional implementation of the mean filter. Our method shows up to one order of magnitude improvement in processing speed over the conventional method especially on 3D images with large filter masks.